Links between Temperature Biases and Flow Anomalies in an Ensemble of CNRM-CM5.1 Global Climate Model Historical Simulations - O. Lhotka; A. Farda (Advances in Meteorology)
The aim of this study was to evaluate temperature and sea-level pressure (SLP) fields and to analyse a related anomalous flow over midlatitudes simulated by the CNRM-CM5.1 global climate model (GCM). Simulated flow over midlatitudes of the Northern Hemisphere was assessed through flow indices, classified into 11 circulation types. Reference data were taken from the NOAA-CIRES 20th Century Reanalysis, version 2c. CNRM-CM5.1 exhibited analogous temperature biases to those reported for the mean of the CMIP5 GCMs’ ensemble. The most prominent features were an erroneous temperature dipole pattern in the Atlantic Ocean and a warm bias over regions of deep water upwelling (locally exceeding 5°C). The latter feature was associated with negative SLP biases in those regions. Too low pressure was found over midlatitudes of the Northern Hemisphere, and CNRM-CM5.1 simulated too frequent zonal flow in these latitudes. The usage of three ensemble members with different initial conditions did not improve model’s outputs because the bias is found to be considerably larger compared to the ensemble members’ spread. The study showed that temperature and SLP biases are connected in certain regions, suggesting that improvement of GCMs and development of bias correction methods should be carried out with a complex insight.